Tablet-like semi-finished product comprising plastic matrix and thermoplastic film

By adopting a combination technology of potentially reactive plastic composition and thermoplastic film in fiber-reinforced sheet-like semi-finished products, the problems of low stability in the lateral direction and limited diversity of substrates are solved, and higher stability and broader substrate adaptability are achieved.

CN119562983APending Publication Date: 2025-03-04NOLAX
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380056689.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-02
Filing Date
2023-07-17
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing fiber-reinforced sheet-like semi-finished products have low stability in the lateral direction of the fiber and have limited substrate diversity, making it difficult to meet complex manufacturing needs.

Method used

Using a sheet-like semi-finished product containing a substrate of a potentially reactive plastic composition and continuous fibers, combined with a thermoplastic film, the fibers are embedded in the substrate by spraying or spreading, and fibers are applied on the thermoplastic film to form a multi-layer film structure to improve adhesion.

Benefits of technology

The lateral stability and substrate diversity of sheet-shaped semi-finished products are significantly improved, the tensile strength of composite materials is enhanced, and a wider substrate bonding capacity is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to a flat semi-finished product comprising:-a matrix comprising at least one potentially reactive plastic composition which can be cured to form an elastomer, in particular a thermoplastic elastomer; -continuous fibers embedded in the matrix, wherein the fibers are preferably unidirectionally aligned. The sheet-like semi-finished product further comprises a thermoplastic film. The invention also relates to a method for producing such a sheet-like semi-finished product and to the use of such a sheet-like semi-finished product.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The invention relates to a sheet-like semi-finished product, a method for producing a sheet-like semi-finished product and the use of a sheet-like semi-finished product according to the preambles of the independent claims.

[0002] Fiber-reinforced plastics are becoming increasingly important in the production of structural components. Such components are particularly suitable for use in motorsports, aerospace, rail vehicles and aircraft construction. For example, these components have a lower weight than conventional components made of steel, aluminum or wood while maintaining the same performance, which results in savings in energy and fuel consumption.

[0003] For example, fiber-reinforced plastics can be obtained by embedding the fibers in a plastic matrix and then curing them. Thermosetting resin systems predominate as plastic matrices. Alternatively, the fibers and resin can be combined with a suitable hardener and stored in the uncured state. Crosslinking to form the fiber-reinforced plastic then takes place only at a later stage. Epoxy resins are often used as resins. However, due to the presence of hardeners and accelerators in the resin matrix, they can only be stored for a limited time. In order to prevent premature crosslinking, such reaction systems are stored at low temperatures (approximately -20 ° C) and must be thawed before further processing.

[0004] EP 3330311 A1 describes prepregs for producing composite components which consist of fiber materials impregnated with a latently reactive one-component polyurethane and do not contain a resin component.

[0005] WO 2020 / 059476 A1 describes a textile impregnated with a cyanate ester, which can be used, in particular, for producing laminates laminated together with metal foils.

[0006] WO 2019 / 088009 A1 describes a two-layer adhesive tape consisting of a reactive adhesive layer and a reinforcement layer with aligned fibers. The matrix of the fiber-reinforced material does not function as an adhesive.

[0007] WO 99 / 29755 A1 and EP 3730528 A1 describe latently reactive polyurethane systems based on encapsulated isocyanates and carbodiimides. They do not contain long fibers as fillers.

[0008] Fiber-reinforced self-adhesive tapes (duct tape, heavy duty tape) are well known, and there are also versions with aligned (parallel) fibers, so-called filament tapes. These self-adhesive tapes have in common that they are applied only by pressure, without temperature requirements, and are not equipped with latently reactive adhesives for the fiber reinforcements, if they are in separate layers at all.

[0009] Long fiber reinforced composites are also well known, which have a thermoplastic or thermosetting (and already crosslinked) matrix. Such (continuous) fibers are aligned using extrusion or pultrusion methods.

[0010] For example, WO 2018 / 234423 A1 describes a sheet-like semi-finished product made from a plastic matrix containing embedded unidirectionally aligned continuous fibers.

[0011] The main disadvantage of unidirectional tapes is their low stability in the transverse direction of the fibers. The matrix, which has not yet been crosslinked, has a very low viscosity and therefore offers almost no shear resistance during bonding or pre-coating. The combinations and types of substrates that can be bonded are very limited.

[0012] Therefore, at least one object of the present invention is to overcome the disadvantages of the prior art. Specifically, the object of the present invention is to provide a sheet-like semi-finished product with particularly high stability and capable of achieving a high substrate diversity. The object of the present invention is also to provide a method for producing such a sheet-like semi-finished product and the use of such a product.

[0013] These objects are achieved by the devices, methods and uses defined in the independent patent claims. Further embodiments result from the dependent patent claims.

[0014] The present invention relates to a sheet-like semi-finished product, comprising:

[0015] - a matrix comprising at least one latently reactive plastic composition which can be cured to form an elastomer, in particular a thermoplastic elastomer,

[0016] - Continuous fibers embedded in a matrix, wherein the fibers are preferably aligned unidirectionally.

[0017] The sheet-like semi-finished product further comprises a thermoplastic film.

[0018] The term "embedded" relates to a macroscopic perspective, i.e. an external perspective. In particular, "embedded" means impregnated. The fibers are coated with the matrix. The coating can be done, for example, by spraying with the matrix or by pulling the fibers through a matrix solution.

[0019] In the context of this application, continuous filaments are all fibers with a length ≥ 50 mm.

[0020] Elastomers, particularly thermoplastic elastomers, can have soft segments and hard segments.

[0021] The thermoplastic film is preferably substantially inseparably bonded to the substrate, ie the film cannot be removed and reused. More precisely, there is a permanent bond between the film and the substrate.

[0022] The semi-finished product according to the invention is characterized by improved stability, in particular in the transverse direction of the fibers. It has been shown that despite the fact that the thermoplastic layer, ie the film, itself has no fiber reinforcement, the tensile strength of the entire composite material can be significantly increased. As a result, the positive mechanical properties of the fiber layer are transferred to the entire sheet-like semi-finished product.

[0023] The plastic consistency of the molten thermoplastic adhesive layer can absorb shear forces.

[0024] In addition, the semi-finished product according to the invention has the advantage that a wider variety of substrates can be bonded. Surprisingly, good adhesion was found between the two layers - plastic matrix and thermoplastic film. After drying of the latent reactive matrix and most importantly after bonding of the two substrates, both provide sufficiently good initial adhesion. A clever arrangement of these layers results in an almost unlimited variety of substrates. For example, the semi-finished product according to the invention can be bonded to metals or non-reinforced plastics to form a composite material.

[0025] The advantage of latently reactive plastic compositions is that the two processes of pre-coating and bonding can be easily separated.

[0026] The thermoplastic film can be a multilayer film. The multilayer film can have different surface properties, especially on its outer surface. This allows the semi-finished product to be adapted to the desired application.

[0027] The thermoplastic film may consist of at least one nonpolar layer comprising at least one nonpolar polymer and at least one polar layer comprising at least one polar polymer.

[0028] For the purposes of this application, non-polar refers to materials and / or surfaces with a surface tension of less than 35 mN / m. For the purposes of this application, polar refers to materials and / or surfaces with a surface tension of more than 37 mN / m. The surface tension can be determined using commercially available test inks. Various test series are defined according to DIN 53364. Another way to determine the surface tension is to measure the so-called contact angle or wetting angle. This involves measuring the angle between the surface and a water droplet. The better the wettability of the surface, the smaller the angle. The angle is measured, for example, using a goniometer.

[0029] Preferably, the at least one polar layer faces the embedded continuous fibers in the matrix.The polar layer is particularly compatible with the matrix and thus forms a particularly stable composite material.

[0030] Preferably, the at least one non-polar polymer is selected from the group consisting of polypropylene, modified polypropylene, polyethylene, modified polyethylene, polyoxymethylene, ethyl vinyl acetate, styrene block copolymers, ionomers, olefins, rubbers or plastomers and copolymers thereof.

[0031] Preferably, the at least one polar polymer is selected from the group consisting of polyamide, copolyamide, polyester, copolyester, polyurethane, polyether block amide, acrylate or polycarbonate. Particularly preferably, the polar layer comprises acrylonitrile-butadiene-styrene copolymer (ABS) and its mixture with polycarbonate (ABS / PC), polyamide (PA) or polyurethane (TPU), or consists of acrylonitrile-butadiene-styrene copolymer (ABS) and its mixture with polycarbonate (ABS / PC), polyamide (PA) or polyurethane (TPU).

[0032] The plastic composition may comprise a polyurethane and a latently reactive, in particular encapsulated, surface-deactivated or blocked isocyanate. Radiation-crosslinkable isocyanates are also feasible. The quantitative ratio between polyurethane and isocyanate may vary. For example, the following composition of surface-deactivated isocyanates may be considered: for 100 parts by weight (pbw) of polyurethane, 5 to 10 pbw of toluene-2,4-diisocyanate dimer (TDI dimer) may be added. 15 pbw of isophorone diisocyanate trimer (IPDI trimer) may also be added to 100 pbw of polyurethane to prevent yellowing of the material. Blocked isocyanates may also be used. For example, 2 to 15 pbw (dimethylpyrazole) blocked hexamethylene-4,6-diisocyanate (HDI) trimer may be added to 100 pbw of polyurethane.

[0033] Due to the latently reactive isocyanates, there is no reaction between isocyanates and the free OH groups of the polyurethane at room temperature. The sheet-like semi-finished products can be stored for a long time at room temperature without any effort. The reaction process, i.e. the reaction with the surface-activated isocyanates, can be carried out by briefly starting the reaction at low temperatures (<120°C). However, blocked isocyanates can be used, which can only be activated at higher temperatures, for example at temperatures above 120°C. The shaping process (e.g. pressing, vacuum bag method or in autoclave) can still be kept short. Short cycle times can be used, which has a positive effect on the available fibers. Therefore, low-melting fiber types such as polyamide, polyethylene or polyester can also be used.

[0034] The plastic composition may comprise a polyurethane and a latently reactive carbodiimide. Such plastic compositions are described in WO 99 / 29755 A1 and EP 3730528 A1.

[0035] Preferably, the plastic composition is a dispersion, particularly preferably an aqueous dispersion. The plastic composition can also be in the form of a powder or a melt. The dispersion can be applied, for example, by spraying, knife coating, soaking, pouring and / or vacuum infusion. However, the fibers can also be pulled through the dispersion solution and spread in the process. The dispersion promotes fiber spreading. This can increase the degree of wetting, achieve optimal fiber incorporation and a high fiber content in the matrix.

[0036] Fibers can be based on proteins, cellulose, synthetic polymers or inorganic substances.

[0037] The protein based fibres may be selected from: wool, silk, angora, cashmere, casein, collagen, ardein and zein.

[0038] Cellulosic fibers can be cotton and bast fibers, such as cotton, flax, hemp or jute. Cellulosic fibers can also be wood-based, such as viscose, modal, lyocell, cupro, acetate.

[0039] The fibers made of synthetic polymers may be selected from: polyethylene, polyester; polyamide; aramid; polypropylene; polyurethane (elastane); acrylic; polytetrafluoroethylene; polyphenylene-2,6-benzobisoxazole; liquid crystal polymers (LCP), in particular poly(p-hydroxybenzoic acid-co-hydroxy-6-naphthoic acid).

[0040] The group of fibers made of inorganic substances includes carbon, ceramics, glass, quartz, and metals.

[0041] The fibers can be embedded in the matrix as individual fibers or can have been previously spun into threads and embedded as threads. The fibers can also be processed into threads and then into fabrics and thus embedded in fabrics. Filaments can also be embedded. Filaments are man-made fibers of any length. It is also conceivable that combinations of different fibers can be embedded.

[0042] Being able to use different types of fibers has the advantage of opening up a wide range of applications. The properties of the product can be optimally adapted to the intended use.

[0043] The fibers are preferably arranged substantially along the longitudinal extension of the main surface of the semi-finished product. Preferably, the fibers are aligned unidirectionally. "Unidirectional" is understood here to mean that the longitudinal axes of the fibers are substantially parallel. "Substantially parallel" is understood to mean that the longitudinal axes of the fibers do not include an angle of more than ±25° to each other. Preferably, the angle between the longitudinal axes of the fibers is less than ±10°.

[0044] The advantage of unidirectional semi-finished products is that they can be layered in a targeted manner along the force path. If a plurality of sheet-like semi-finished products, each with unidirectionally aligned fibers, are layered and twisted relative to one another, this results in a particularly high resistance to mechanical actions from different directions.

[0045] The fibers of the sheet-like semi-finished product are preferably spread. Spread fibers can be better wetted, the fiber incorporation and thus the fiber content are increased. A higher fiber content increases the properties of the fiber composite component. Fiber spreading also makes it possible to use different types of fibers in the semi-finished product. It is also conceivable to use different plastic compositions in the semi-finished product. This makes it possible to combine different properties in the material.

[0046] The thermoplastic film may contain further additives selected from the group consisting of fillers, processing aids, stabilizers, dyes or combinations thereof. Possible fillers include in particular glass fibers, chalk or talc.

[0047] The matrix may further comprise other additives selected from the group consisting of thermoplastic polymers, fillers, processing aids, stabilizers, dyes or combinations thereof. The thermoplastic polymer may be, for example, a polyolefin, ethyl acrylic acid (EAA), ethylene vinyl acetate (EVA), polyvinyl acetate (PVA), (co)polyester, (co)polyamide, styrene copolymers, acrylates, polyvinyl alcohol or combinations thereof.

[0048] Another aspect of the present invention relates to a method for manufacturing a sheet-like semi-finished product, in particular a sheet-like semi-finished product as described above. The method comprises the following steps:

[0049] a) embedding the fibers in a matrix comprising at least one latently reactive plastic composition which can be cured to form an elastomer,

[0050] b) Applying the embedded fibers to a thermoplastic film.

[0051] The thermoplastic film may be a multilayer film, in particular a multilayer film as described above.

[0052] The thermoplastic film may comprise at least one non-polar layer comprising at least one non-polar polymer and at least one polar layer comprising at least one polar polymer. The non-polar polymer may be selected from the group as described above. The polar polymer may be selected from the group as described above.

[0053] Preferably, the embedded fibers are applied to at least one polar layer of the multilayer membrane.

[0054] Advantageously, in step a), the fibers are spread for embedding. Spreading increases the degree of wetting of the fibers. Optimization of fiber incorporation. It is also possible to coat individual fibers with different plastic compositions. This allows the combination of further properties in the semi-finished product.

[0055] The spreading and impregnation of the fibers are described in WO2018 / 234423A1, the contents of which are incorporated herein. The impregnated fibers can be placed on a thermoplastic adhesive layer before drying. For this purpose, a film is fed from below, the moistened, aligned fibers are placed on it, and the film / fiber combination is passed through an oven to film the substrate (drying). Thus, according to a T peel test based on DINEN ISO 11339, the fibers form an adhesive force of 0.1-1.0 N / mm. This adhesive force is sufficient to ensure further processing into an adhesive layer reinforced with potentially reactive fibers without detaching the fibers from the film before actual bonding.

[0056] The adhesion can be established by crosslinking the matrix in the actual bonding step. The adhesion can then sometimes increase to values ​​above 1.0 N / mm, especially if the chemistry of the matrix and the chemistry of the top film layer are compatible.

[0057] This production method leads to even higher adhesion than when the membrane and the unidirectional fiber-reinforced adhesive layer are produced separately and only laid together in the bonding process. The adhesion values ​​are approximately 50% higher.

[0058] Without wishing to be bound by theory, the increased adhesion may be due to a crosslinking process of the matrix. In a sandwich structure (stack), the matrix must wet the membrane surface, for which low viscosity is advantageous. At the same time, crosslinking begins with bonding, which leads to an increase in viscosity. This means that optimal wetting is hindered by simultaneous wetting.

[0059] On the other hand, if the matrix (and with it the fibers) is applied in the form of a dispersion, the film is optimally wetted and remains optimally wetted even after the matrix has dried. Wetting and crosslinking are separated in time, which leads to higher adhesion values ​​despite the same chemical composition.

[0060] After step b), drying may be carried out at a temperature of up to 50°C, preferably up to 35°C.

[0061] It is also advantageous if the membrane is pretreated before step b). The pretreatment can be performed with corona, plasma or flame treatment. The pretreatment optimizes the wetting of the membrane. The pretreatment can be particularly useful for membranes with non-polar polymers to ensure optimal wetting and adhesion.

[0062] Another aspect of the invention relates to a sheet-like semi-finished product, in particular a sheet-like semi-finished product as described above, which can be produced by the method described above.

[0063] Another aspect of the invention relates to the use of the above-mentioned sheet-like semi-finished product for the production of clothing, vehicle parts, tires, sports and leisure goods, tools, suitcases, machine parts, drive and conveyor belts, packaging, architectural membranes, repair materials.

[0064] Another aspect of the invention relates to a composite material comprising a sheet-like semi-finished product as described above and a metal layer and / or a plastic layer, preferably a non-fiber-reinforced plastic layer. The plastic may also be fiber-reinforced.

[0065] The metal layer can be made of, for example, aluminum, aluminum alloys, iron, iron alloys, in particular steel, galvanized steel and stainless steel, copper, copper alloys, titanium, titanium alloys, magnesium, magnesium alloys, tin, tin alloys, lead, lead alloys, bronze, brass. The metal can be painted, in particular KTL painted, passivated, anodized, electrolytically, galvanized, chrome-plated or subjected to other surface treatments.

[0066] Non-fiber reinforced plastics can be, for example, polyethylene, polypropylene, polyamide, polyester, polyoxymethylene, polystyrene, polyphthalamide, polyphenylene sulfide, polyetherketone, polyimide, polysulfone, polycarbonate, polymethyl acrylate, styrene acrylonitrile, acrylonitrile butadiene styrene, polyvinyl acetate, polyvinyl chloride, thermoplastic elastomers, rubber and mixtures thereof. Plastics can be reinforced with minerals, in particular calcium carbonate and talc, silicon dioxide, kaolin, carbon black, glass beads, titanium dioxide, carbon nanotubes, elastomers and duromers.

[0067] The composite material can be produced using the above-described method, wherein the sheet-shaped semifinished product is additionally bonded to a metal layer and / or a plastic layer, preferably a non-fiber-reinforced plastic layer.

[0068] The sheet-like semi-finished product according to the invention can be used in various bonding applications together with other materials, making it possible to produce different composite materials for different applications.

[0069] The invention is explained in more detail in the examples which follow. These examples should not be construed as limiting. Example

[0070] Dispersion 1 is an aqueous anionic dispersion of an aliphatic polyurethane consisting of Dispercoll® U 56 (available from Covestro, Leverkusen, Germany) and surface-deactivated Desmodur® Z 2589 (available from Covestro, Leverkusen, Germany). The solids content was about 60%.

[0071] Dispersion 2 is an aqueous anionic dispersion of an aromatic polyurethane consisting of Dispercoll® U 56 (available from Covestro, Leverkusen, Germany) and surface deactivated Dispercoll® BL XP 2514 (available from Covestro, Leverkusen, Germany). The solids content was about 60%.

[0072] Hytrel® 4056 (available from DuPont, Wilmington, USA) was used to extrude a 30 g / m 2 The flat film is regarded as a monofilm.

[0073] The multilayer film used was nolax® A22.5016, a PP / TPU film with a basis weight of 60 g / m 2 (Available from nolax, Sempach-Station, Switzerland). Coating and bonding are done on the TPU side.

[0074] To impregnate the fibers, Twaron® filament yarn (available from Twaron Teijin, Arnhem, the Netherlands) was spread over several deflecting rollers on a fiber spreading machine. The spread fibers were then impregnated with an aqueous dispersion, either Formulation 1 or 2, using two coating rollers and deposited on a single or multilayer film. This was then dried at a maximum temperature of 35°C.

[0075] Bonding was carried out on a Meyer press at a temperature of 50°C (uncrosslinked precoat) or 140°C (crosslinked bonding), a pressing time of 2 minutes and a pressure of 5 bar. A non-elastic cotton fabric was applied to the thermoplastic adhesive layer side using a suitable adhesive. This served to fix the adhesive layer in the T-peel test.

[0076] For comparison, samples were also bonded with prefabricated latently reactive unidirectional tapes. These tapes were placed on a BOPP carrier and placed on the adhesive layer after drying during the bonding process. They were therefore not pre-fixed.

[0077] The following samples were manufactured:

[0078]

[0079] T peel test

[0080] T-peel tests were performed according to DIN 53357 at 23° C. and 50% relative humidity at a peel speed of 100 mm / min on a Zwick type 1120.25 tensile testing machine on specimens 25 mm wide and 250 mm long.

[0081] The following release strengths were determined:

[0082]

[0083] Comparison of Sample A with Sample B, Sample C with Sample D, and Sample G with Sample H shows the positive impact of spreading the fibers directly onto the hot melt adhesive film compared to laminating a prefabricated unidirectional fiber reinforced adhesive layer onto the same hot melt adhesive film.

[0084] Comparison of sample A with sample E shows that the same release strength can be achieved by careful pre-coating of the latently reactive unidirectional fiber reinforced adhesive layer and simultaneous pressing. However, comparison with sample B shows that wetting is not as good by pre-coating as when the fibers are applied directly to the film and the dispersion is dried on the film. This means that even for sample E, some optimal wetting is lost despite pre-coating due to the onset of crosslinking during the bonding process.

[0085] Comparison of sample B with sample F shows that simple fixation of the fibers in the thermoplastic film leads to significantly lower release strength than with the use of a matrix. The viscosity of the thermoplastic adhesive film is too high to allow good fiber wetting.

[0086] Tensile strain testing

[0087] The following samples were manufactured:

[0088]

[0089] Sample I is the unidirectional fiber reinforced adhesive layer used in Samples A, E, and G. Sample J is Sample B which has not been crosslinked.

[0090] The following tensile strengths and elongations at break transverse to the grain direction were found:

[0091]

[0092] Sample I broke immediately at the start of the test.

[0093] Sample I clearly shows that unidirectional fiber-reinforced adhesive layers without adhesive film are very sensitive to loads transverse to the fiber direction, which makes the application technology challenging and the tape easily damaged.

[0094] Sample J, on the other hand, showed a tensile strength and elongation at break that are typical for a thermoplastic adhesive layer. The processing was therefore no different from the processing of films without fiber reinforcement.

Claims

1. A sheet-like semi-finished product, comprising: - a matrix comprising at least one latently reactive plastic composition which can be cured to form an elastomer, in particular a thermoplastic elastomer, - continuous fibers embedded in said matrix, wherein said fibers are preferably aligned unidirectionally, It is characterized in that The sheet-like semi-finished product further comprises a thermoplastic film.

2. The sheet-like semi-finished product according to claim 1, wherein the thermoplastic film is a multilayer film.

3. The sheet-like semifinished product according to claim 2, wherein the thermoplastic film consists of at least one nonpolar layer comprising at least one nonpolar polymer and at least one polar layer comprising at least one polar polymer.

4. The sheet-like semi-finished product according to claim 3, wherein the at least one polar layer faces the continuous fibers embedded in the matrix.

5. The sheet-like semi-finished product according to claim 3 or 4, wherein the at least one non-polar polymer is selected from the group consisting of polypropylene, modified polypropylene, polyethylene, modified polyethylene, polyoxymethylene, ethyl vinyl acetate, styrene block copolymers, ionomers, olefins, rubbers or plastomers and copolymers thereof.

6. The sheet-like semifinished product according to any one of claims 3 to 5, wherein the at least one polar polymer is selected from the group consisting of polyamides, copolyamides, polyesters, copolyesters, polyurethanes, polyether block amides, acrylates or polycarbonates.

7. The sheet-like semifinished product according to any one of the preceding claims, wherein the plastic composition comprises a polyurethane and a latently reactive, in particular encapsulated, surface-deactivated or blocked isocyanate.

8. The sheet-like semifinished product according to any one of the preceding claims, wherein the plastic composition comprises a polyurethane and a latently reactive carbodiimide.

9. A method for producing a sheet-like semi-finished product, in particular a sheet-like semi-finished product according to any one of claims 1 to 8, comprising the following steps: a) embedding the fibers in a matrix comprising at least one latently reactive plastic composition which can be cured to form an elastomer, b) Applying the embedded fibers to a thermoplastic film.

10. The method of claim 9, wherein the thermoplastic film is a multilayer film.

11. The method according to claim 10, wherein the thermoplastic film consists of at least one non-polar layer comprising at least one non-polar polymer and at least one polar layer comprising at least one polar polymer.

12. The method of claim 11, wherein the embedded fibers are applied to at least one polar layer of the multilayer membrane.

13. The method according to any one of claims 9 to 12, wherein the fibers are spread before embedding in step a).

14. The method according to any one of claims 9 to 13, wherein the membrane is pretreated prior to step b).

15. Use of the sheet-like semi-finished product according to any one of claims 1 to 8 for the production of clothing, vehicle parts, tires, sports and leisure goods, tools, suitcases, machine parts, architectural membranes, jewelry, drive and conveyor belts, packaging, building materials, repair materials.

16. A composite material comprising a sheet-like semifinished product according to any one of claims 1 to 8 and a metal layer and / or a plastic layer, preferably a non-fiber-reinforced plastic layer.

Citation Information

Patent Citations

  • Latent reactive adhesive preparations

    EP3730528A1

  • Method for producing and using storage-stable, latent-reactive layers or powders of surface-deactivated, solid polyisocyanates and dispersion polymers with functional groups

    WO1999029755A1

  • Sheetlike semifinished product having a plastics matrix

    WO2018234423A1

  • Laminate and reinforcing sheet

    WO2019088009A1

  • Cyanic acid ester compound, method for producing same, resin composition, cured product, single-layer resin sheet, multilayer resin sheet, prepreg, metal foil-clad laminate, printed wiring board, sealing material, fiber-reinforced composite material, adhesive and semiconductor device

    WO2020059476A1